Video Assemblages: ‘Machinic Animism’ and ‘Asignifying Semiotics’ in the Work of Melitopoulos and Lazzarato - Jay Hetrick (Footprint)
In this paper I will analyse the theoretical background of a single video installation – co-created by Angela Melitopoulos and Maurizio Lazzarato – in order to unpack Deleuze and Guattari’s important but somewhat elusive concepts of ‘machinic animism’ and ‘asignifying semiotics.’ Assemblages (2010) is a three channel audio-visual documentary about the French philosopher and psychoanalyst Félix Guattari. I will argue that, in order to fully understand this work, we must interrogate the incredibly dense theoretical context it inhabits. In particular, I will explore the juncture between Guattari’s ethico-aesthetic ideas concerning a potential ‘ecosophy’ – or theory of the different relations between humans and nature that depends upon a new semiotics – and Lazzarato’s conception of ‘videophilosophy,’ which is grounded upon a politicised Bergsonian onto-aesthetics. I will conclude by criticizing Nicolas Bourriaud’s misappropriation of Guattari in his book Relational Aesthetics and propose that Assemblages demands quite a different and more radical gesture of relationality: one that follows an ecosophical logic that envelopes and imbricates the different levels of nature, the individual, and the social in a way that we might qualify with the term ‘unnatural participation.’